Missing : a Novel - Harris, Lisa 1969- (Grand Rapids, Michigan : Revell, a division of Baker Publishing Group, 2016)
Lucy Hudson goes missing after her husband is found murdered. Special Agent Nikki Boyd doesn't know who to trust as her search for Lucy plunges her into a deadly world of counterfeit drugs.
Keywords: Women detectives -- Fiction; Missing persons -- Fiction -- Investigation; Murder -- Fiction -- Investigation; Nashville (Tenn.) -- Fiction; Tennessee -- Fiction; Christian fiction; Religious fiction; Romantic suspense fiction; Detective and mystery fiction; Thrillers (Fiction)